Effect of Gelatine and Citric Acid in the Glycerol Containing Edible Coating Used For Storage of Tomato - Rudito, Rudito (Fakultas Teknologi Pertanian Universitas Brawijaya, 2005)
A fresh is perishable mainly due its high respiration rate. This research was conducted to examine the use of gelatine and citric acid in the glycerol containing edible coating to reduce the rate of deterioration of tomatoes during storage at room temperature. The use of edible coating is expected to be able to substitute a low temperature storage which is more expensive. The respective concentrations evaluated were 10%, 12% and 14% for gelatine and 0,5%, 0,7% and 0,9% for citric acid. The experiment was run in triplicates employing a factorial completely Randomized Block Design using a breaker ripe stadium tomatoes of Intan variety grown in Malang regions. The treated tomatoes were stored at room temperature until a red ripe stadium was achieved. The results indicated that all the 9 treated samples were able to reach a red ripe stadium with some variations of quality after 15 days of storage. In general, the treated samples show a higher rate of respiration and higher level of vitamin C, but were firmer in texture and a lower level of weight lost than the ones of control. It was found that the use of 14% (w/v) gelatine and 0,9% (w/v) citric acid in a combination with 5% glycerol is the most effective to use as an edible coating for tomatoes stored at room temperature (26-29oC). The lost of the above-mentioned quality attributes is still minim after 15 days storage. Â Key Words: Tomatoes, Edible coating, Respiration